Concurrent infections of Flavobacterium columnare and Edwardsiella ictaluri in striped catfish, Pangasianodon hypophthalmus in Thailand - Ha Thanh Dong (2018)
© 2015 Elsevier B.V. Flavobacterium columnare and Edwardsiella ictaluri are two major bacterial pathogens threatening catfish aquaculture globally. Earlier studies have focused on the characterization of single bacterial infection. In reality, multiple bacterial pathogens are present in aquaculture systems and are probably responsible for disease outbreaks and considerably outweigh single infection. The objectives of this study, therefore, were to investigate whether single or concurrent bacterial pathogens were involved in naturally diseased striped catfish (Pangasianodon hypophthalmus) and subsequently investigate the pathogenicity of single- and dual-infection through experimental challenges. The investigation revealed coinfections of F. columnare and E. ictaluri found in naturally diseased Thai striped catfish exhibiting columnaris and edwardsiellosis diseases. Bacterial identification was confirmed by phenotypic tests, species-specific PCR and 16S rDNA sequence analysis. Molecular data analysis also identified that the infected fish species was P. hypophthalmus. Experimental challenges of striped catfish juveniles with single and dual bacterial species using both immersion (i.m) and injection (i.p) approaches were performed. Injection of two different doses of combined bacteria caused markedly high mortality of 86.7-100%, indicating high virulence of the bacterial isolates. Immersion (i.m.) coinfection of E. ictaluri (2.6×106CFUmL-1) and F. columnare (1.0×104CFUmL-1) caused significantly high cumulative mortality (96.7±5.8%) compared to i.m. of single infection of E. ictaluri (80.0±20%) or F. columnare (3.3±5.7%) with the same dose of bacteria. Both coinfection challenge routes i.p. and i.m. successfully mimicked typical signs and histopathological manifestations of natural coinfection. This study had fulfilled Koch's postulates through single- or dual-challenged tests to mimic the natural disease case in striped catfish. Statement of relevance: The authors strongly believe that our manuscript would provide significant knowledge to fish aquaculture especially to that of the striped catfish P. hypophthalmus.